Analytical Method Development and Validation of Tadalafil and Dapoxetine Hydrochloride in Combined Tablet Dosage Form by Rp-Hplc (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
The analytical method was developed and validated for determination of Tadalafil and Dapoxetine hydrochloride in combined tablet dosage form by reversed phase high performance liquid chromatography. Thseparation was carried out on SHIMADZU-LC 20AT Column C18 (240 × 4.6mm) 5μm. The mobile phase consists of Acetonitrile: water and0.1 ml triethylamine and 0.5% trifluroacetic acid 75:25 (v/ v) in the ratio of 75:25 at flow rate 1 ml/ min with UV visible detector wavelength at 288nm. The column temperature calibration curve was linear over the concentration range 80-120% μg/ml(r 2 =1). The validation was carried out as per ICH guidelines. The development method was Rapid, Specific, Precise, Accurate, Linear can be used for routine analysis of these drugs from tablet formulation.
Keywords: Tadalafil; Dapoxetine hydrochloride; RP-HPLC; validation; Method development; 288nm and UV Visible detector